The exclusion of the right to access public policy determined by the adopted agricultural zoning method - the case of conilon coffee farmers from the municipality of Vargem Alta-ES - Feitoza, Leandro Roberto; NAGATANI FEITOZA, HIDEKO; Rocha de Oliveira, Vagner; Carreiro Ribeiro, Vera; Belo Barbosa, Fabiano (Geografares, 2016)
The municipality of Vargem Alta requested Ministry of Agriculture, Livestock and Food Supply (MAPA) for their inclusion in the conilon coffee zoning. The discontent of local farmers with this exclusion was the first indication that the information used in the zoning by MAPA was insufficient to reveal the appro-priate ecosystems for the cultivation of this species. The Natural Zones employed to define the suitable environments for conilon cultivation and the field crop checks to confirm the species, were the basis of this study which was used by MAPA to review the decision to include Vargem Alta in the conilon coffee zoning. MAPA published this addition in the Official Gazette of 04/10/2012 giving the local farmers the right to benefit from public policies that are related to this subject. It is suggested that alterations are applied to the legal documents concerning agricultural zoning, with the aim of authorising the inclusion of those beneficiaries who are excluded due to limitations of the zoning method used. Keywords: Agroecological zoning. Coffee farmers benefits. Social and productive inclusion.